PENGARUH KUALITAS PRODUK, HARGA DAN DIGITAL MARKETING TERHADAP MINAT BELI KONSUMEN PADA KAYU MEBEL - Ririn Wahyuningsih; Agus Suyatno; Indra Hastuti (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
In the era of globalization, manufacturing companies operating in the furniture industry promise business opportunities and challenges for companies. With the era of globalization, product markets will expand and on the other hand, this situation will give rise to increasingly fierce competition in industry. In order for this goal to be achieved, every company must strive to produce quality products that customers want and provide affordable prices. Thus, every company must be able to understand the company's survival as an organization to try to meet customer needs and desires. This research aims to determine the influence of product quality, price and digital marketing on consumer buying interest at the ud babe narwan boyolali wood furniture company. the population in this study were buyers of wooden furniture products from UD. Babe Narwan Boyolali. The sample taken was 100 respondents using a purposive sampling technique through a questionnaire distributed via Google Forms and filled in by consumers. Testing the hypothesis through the (partial) t test obtained the result that the product quality variable had a positive and significant effect on consumer buying interest as evidenced by a significance value of 0.000 <0.05. The price variable has a positive and significant effect on consumer buying interest as evidenced by a significance value of 0.008 < 0.05. The digital marketing variable has a positive and significant influence on consumer buying interest as evidenced by a significance value of 0.003 <0.05. The results of the F Test (Simultaneous) in this research obtained a calculated F value of 34.446.